Prolonged exposure to cocaine self-administration results in a continued progression of alterations in functional activity in a nonhuman primate model - Linda J. Porrino; Hilary R. Smith; Thomas J.R. Beveridge; Mack D. Miller; Susan H. Nader; Michael A. Nader (Drug and Alcohol Dependence Reports, 2023)
Background: Studies of nonhuman primates with exposures of up to 100 days of cocaine self-administration (SA) have provided evidence that the central effects of cocaine progress over time. These durations of cocaine exposure, however, may be insufficient to capture the extent of the neurobiological alterations observed in cocaine users, many of whom use the drug for years. The goal of the present study was to determine whether 1.5 years of cocaine SA would result in further progression of alterations in functional brain activity. Methods: Adult male rhesus monkeys were exposed to 300 sessions of high-dose cocaine SA over 1.5 years. Following the final session rates of local cerebral glucose utilization (LCGU) were assessed with the 2-[14C]-deoxyglucose method and compared to rates of LCGU in control monkeys who responded for food reinforcement. In addition, LCGU in these animals was compared to a previously published group of monkeys that had self-administered cocaine or food for 100 sessions over a 4–5 month period. Results: Compared to 100 days of exposure, 300 days of cocaine SA further reduced LCGU in the post-commissural striatum and produced reductions in areas unaffected by the shorter duration of exposure, such as the hypothalamus, all of the amygdala, and large expanses of cortex. Conclusions: These findings demonstrate a clear progression of the impact of cocaine on functional activity with increasing durations of drug experience and have important implications for the development of potential strategies for the treatment of cocaine use disorder.